Diary of a Wimpy Kid: The Getaway (book 12) - Kinney, Jeff (London: Penguin Random House UK, 2017)
Greg Heffley and his family are getting out of town. With the cold weather setting in and the stress of the Christmas holiday approaching, the Heffleys decide to escape to a tropical island resort for some much-needed rest and relaxation. A few days in paradise should do wonders for Greg and his frazzled family. But the Heffleys soon discover that paradise isn't everything it's cracked up to be. Sun-poisoning, stomach troubles and venomous creatures all threaten to ruin the family's vacation.
English.